AKTIVITAS FOTOPROTEKTIF IN VITRO SEDIAAN KRIM EKSTRAK HERBA PUTRI MALU (Mimosa pudica L.) SEBAGAI TABIR SURYA - In Rahmi Fatria Fajar; Dewi Rahma Fitri; Yulis Adriana; Handawati Silitonga; Pra Panca Bayu Chandra (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2026)
The sensitive plant (Mimosa pudica L.) has great potential as a raw material for cosmetics due to its bioactive compounds that can neutralize free radicals. One of its applications is as a sunscreen agent that protects the skin from the harmful effects of the sun’s ultraviolet (UV) radiation. This study aims to determine the Sun Protection Factor (SPF) value of a 70% ethanol extract of the sensitive plant, formulate it into a cream, and evaluate the physical characteristics and sunscreen activity of the formulation. The in vitro SPF value was calculated using UV-Vis spectrophotometry based on the Mansur formula. The cream formulations were prepared in four variations with different extract concentrations: F0 (0%), F1 (0.3%), F2 (0.6%), and F3 (0.9%). Physical evaluation of the formulations included organoleptic testing, homogeneity, spreadability, pH, and viscosity. The results of the physical evaluation showed that all four formulations exhibited good homogeneity. The spreadability test yielded results that met the requirements (5–7 cm), and the pH test results fell within the safe range for the skin (4.5–6.5). The viscosity of the creams decreased as the concentration of the added extract increased. The SPF test results for the cream formulations showed the following values: F0 at 1.8810 (no protection), F1 at 14.2306 (maximum protection category), F2 at 27.2598 (ultra protection category), and F3 at 33.1475 (ultra protection category). Conclusion: A 70% ethanol extract of the putri malu herb was successfully formulated into a sunscreen cream that meets physical quality requirements, and increasing the extract concentration significantly enhanced its photoprotective activity, reaching the ultra protection category.